Interstitial Lung Disease-Complicated Anti-MDA5 Antibody in Clinically Amyopathic Dermatomyositis Patients: Report of Two Cases With Distinct Clinical Features - Pacot, Laurence; Pouchot, Jacques; De Prost, Nicolas; Senant, Marie; Tartour, Eric; Le Pimpec-Barthes, Françoise; Israel-Biet, Dominique; Dragon-Durey, Marie-Agnes (Frontiers in Medicine, 2020)
Two patients presented simultaneously to our hospital with distinct clinical features associated with the presence of anti-MDA5 antibodies: the first one was admitted for a skin rash resembling to a toxic epidermal necrosis (Lyell syndrome) and the second one presented with pulmonary manifestations attributed to a diffuse fibrosing interstitial pneumonitis on chest CT-scan. In addition to the skin lesions involving 40% of the body surface area, the first patient developed a rapid diffuse interstitial pneumonitis with respiratory distress justifying the initiation of a systemic immunosuppressive treatment. However, she died 3 weeks after her admission from mesenteric thrombosis associated with septic shock. The second patient respiratory condition worsened despite an intensive immunosuppressive treatment with high doses of intravenous methylprednisolone and cyclophosphamide and plasmapheresis, and required lung transplantation. Anti-MDA5 antibody titer declined and disappeared on anti-rejection treatment. These two cases underline the diagnostic conundrum and the therapeutic difficulties in patients with anti-MDA5 antibodies and clinically amyopathic dermatomyositis (CADM) or interstitial lung disease (ILD), who may undergo rapidly-progressive and fatal outcome. Presence of anti-MDA5 antibodies should always be suspected when confronted to CADM patients with cutaneous ulcerations or ILD to allow a rapid and adapted treatment initiation.